"Delirium: An essential component in undergraduate training?". (February 2020) - Copeland, Claire; Barron, Derek T.
Abstract: Delirium is an acute medical emergency, the presenting features are significant disturbances in the person's cognition, both their attention and awareness. Delirium develops over a short period of time and predominantly relates to an underlying medical condition. It is significantly under-recognised in the older adults who present to acute medical services and in those living within a care home setting. Up to 30% of older adults who present via the Emergency Department may be experiencing signs and symptoms of delirium, with up to 33% of older adults within the care home setting also experiencing delirium. In both settings the delirium may go unrecognised and be incorrectly considered as a deterioration of an existing dementia. Nurses and care staff in the care home setting, spend more time with older adults than any member of the multi-disciplinary team e.g. GP, physiotherapist, district nurse etc. and as such, their knowledge and skills in the recognition and early intervention when delirium is present can have a significant impact on the outcome for the older adult. Using a Freedom of Information request (Freedom of Information (Scotland) Act, 2002 ), a legal process designed to elicit transparency and guarantee a response, the authors invited responses from Scottish universities, to enable a review of the current approach in the teaching of delirium to undergraduate nursing students. At the outset, the authors were interested to establish the extent to which delirium featured in the nursing undergraduate programme in Scotland. Having established that the approach to teaching was highly variable, this paper poses the question whether more structured focus should be given to the topic within the undergraduate nursing curriculum.